Emerging Role of Histone Acetyltransferase in Stem Cells and Cancer - Daniela Trisciuoglio; Marta Di Martile; Donatella Del Bufalo (Stem Cells International)
Protein acetylation is one of the most important posttranslational modifications catalyzed by acetyltransferases and deacetylases, through the addition and removal of acetyl groups to lysine residues. Lysine acetylation can affect protein-nucleic acid or protein-protein interactions and protein localization, transport, stability, and activity. It regulates the function of a large variety of proteins, including histones, oncoproteins, tumor suppressors, and transcription factors, thus representing a crucial regulator of several biological processes with particular prominent roles in transcription and metabolism. Thus, it is unsurprising that alteration of protein acetylation is involved in human disease, including metabolic disorders and cancers. In this context, different hematological and solid tumors are characterized by deregulation of the protein acetylation pattern as a result of genetic or epigenetic changes. The imbalance between acetylation and deacetylation of histone or nonhistone proteins is also involved in the modulation of the self-renewal and differentiation ability of stem cells, including cancer stem cells. Here, we summarize a combination of in vitro and in vivo studies, undertaken on a set of acetyltransferases, and discuss the physiological and pathological roles of this class of enzymes. We also review the available data on the involvement of acetyltransferases in the regulation of stem cell renewal and differentiation in both normal and cancer cell population.